A Morphological Study of Itbayat Folktales - Yamada, Yukihiro (The Archive, 2025)
The central theme of my paper is to analyze some of the Itbayat folktales from the structural point of view. I shall attempt to demonstrate that the folktale is a structured means of communication as is language, and that there may be a certain pattern of folktales favored by a people, a pattern which may reflect their world view.